PERBANDINGAN PENGATURAN SANKSI PENIPUAN ONLINE BERBASIS ARTIFICIAL INTELLIGENCE: INDONESIA VS AMERIKA - Hendry Widjaya Ong; Windi Afdal; Tantimin (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
This study aims to analyze and compare criminal law regulations pertaining to online fraud utilizing Artificial Intelligence (AI) in Indonesia and the United States. The research focuses on the legal vacuum in Indonesia regarding the handling of AI technology-based fraud crimes, such as deepfakes and voice impersonation. To address this issue, the theoretical frameworks of Progressive Law by Satjipto Rahardjo and Gustav Radbruch’s concept of the Ideal of Law (Rechtsidee) are employed. Data was collected through library research involving legal literature, legislative documents, and actual case studies, and analyzed qualitatively. The findings indicate that the United States has established adaptive regulations addressing AI-based cybercrime, whereas Indonesia still relies on general provisions within the Indonesian Criminal Code (KUHP) and the Electronic Information and Transactions Law (UU ITE), which lack specific provisions for AI-facilitated crimes. This study concludes that Indonesia requires progressive and integrative legal reform to effectively respond to technological challenges and ensure justice, legal certainty, and legal utility for society in the digital era.